Mapping the potential of managed aquifer recharge in Africa: GIS-based multi-criteria decision analysis approach - Ebrahim, Girma Yimer; Stefan, C.; Sallwey, J.; Lautze, Jonathan F. (Elsevier, 2024)
Africa faces numerous challenges related to rainfall variability, droughts, water scarcity, and climate change. Managed Aquifer Recharge (MAR)- groundwater recharge and underground water storage for later use or environmental support presents a viable alternative for water storage and may provide an effective tool for coping with such challenges. However, the potential area where MAR can be feasibly implemented has not been identified. This study mapped MAR feasibility using a Geographic Information System-based Multi-Criteria Decision Analysis (GIS-MCDA) and assessed MAR potential in Africa. The methodology focused on three key pillars of MAR feasibility: intrinsic suitability based on biophysical parameters, water source availability, and water demand. Maps responding to these pillars were developed and combined to create a composite MAR feasibility map. Results show that 18% of the continental area falls into the low feasibility class, 73% into the moderate feasibility class, and 7% into the high feasibility class. The feasibility map was validated against 17 existing MAR schemes in Africa, demonstrating a good correlation between their locations and areas with MAR potential. Results of sensitivity analysis of criteria weights of the biophysical parameters show that geology is the most influential criterion, followed by slope. In general, this first feasibility assessment shows good potential for MAR implementation in Africa. Therefore, MAR should be considered prominently among other water storage options for resilience building in Africa and policymakers should ensure adequate resource allocation for its implementation. The feasibility map can be used to guide MAR planning and investment decisions.